Genome-wide transcriptome profiling revealed biological macromolecules respond to low temperature stress in Brassica napus L - Hussain, Muhammad Azhar; Luo, Dan; Zeng, Liu; Ding, Xiaoyu; Cheng, Yong; Zou, Xiling; Lv, Yan; Lu, Guangyuan (Frontiers in Plant Science, 2022)
Low temperature (LT) influenced the growth, development, distribution and even survival in plants. Brassica napus is a major industrial edible oil crop in the world. LT is a paramount stress factor for this species, and limits large-scale cultivation and production. To dress LT stress problem, apprehension knowledge of the molecular mechanism of LT response is indispensable for rapeseed molecular breeding. The current study involved the Illumina RNA-sequencing technology to investigate the gene expression profiles of Brassica napus in response to LT stress. Brassica napus leaves tissues were sampled, and two cDNA libraries from Control (CK) and LT stressed plants were constructed and sequenced. Our bioinformatics study revealed a total of 79061 unigenes, among these 3703 were differentially expressed genes (DEGs), with 2,129 upregulated and 1,574 downregulated. DEGs were subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes enrichment analyses (KEGG) to pinpoint the LT stress-responsive biological functions and metabolic pathways. These annotated results help identified a diverse range of LT response candidate genes and which were mainly intricated in sugar metabolism, antioxidant defense system, plant hormone signal transduction, and photosynthesis, such as genes encoding sucrose synthase and catabolism, superoxide dismutase (SOD), peroxidase (POD), brassinosteroid signalling kinase, ribulose bis-phosphate carboxylase, cytochrome P450, and ferredoxin. A group of LT stress-responsive transcription factors (TF) with significant divergent expression patterns under CK and LT were reported. A combined protein-protein interaction network suggested that a complex interconnected regulatory network exist in all studied pathways. In a nutshell, RNA-seq data was verified using real-time quantitative polymerase chain reaction analyses (RT-qPCR). This study provides an important pebble in the sea of knowledge to LT response mechanisms and to understand the genetic events of cold response in B. napus.